1993
DOI: 10.1289/ehp.93101252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent exposure to sunlight on melanoma risk among indoor workers and sun-sensitive individuals.

Abstract: Intermittent exposure to sunlight is considered to be an important risk factor for melanoma, but the associations reported in most case-control studies are surprisingly weak. The aim of this study was to evaluate whether the incorporation of a subject's background exposure to the sun and pigmentation characteristics (which are assumed to influence a person's susceptibility to sunlight exposure) could produce stronger associations between sunlight exposure and the risk for melanoma. A population-based case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 6 publications
0
32
0
1
Order By: Relevance
“…The authors defend, among other aspects, that intermittent exposure to the sun could also contribute significantly to the disease. 21 In Brazil, a study carried out in order to identify differences in terms of the most common forms of protection from sun exposure in capitals of the five Brazilian regions found that men, the young (between 15 and 24 years old) and those physically active were most exposed to the sun in all the five regions. 22 In relation to forms of protection, the present study has verified that among those who protect themselves regularly the most common forms of protection are using sunscreen, wearing sunglasses, staying in the shade and using a T-shirt.…”
Section: Graphmentioning
confidence: 99%
“…The authors defend, among other aspects, that intermittent exposure to the sun could also contribute significantly to the disease. 21 In Brazil, a study carried out in order to identify differences in terms of the most common forms of protection from sun exposure in capitals of the five Brazilian regions found that men, the young (between 15 and 24 years old) and those physically active were most exposed to the sun in all the five regions. 22 In relation to forms of protection, the present study has verified that among those who protect themselves regularly the most common forms of protection are using sunscreen, wearing sunglasses, staying in the shade and using a T-shirt.…”
Section: Graphmentioning
confidence: 99%
“…Epidemiological studies reveal a strong association between melanoma formation and sunlight exposure. Whereas squamous and basal cell carcinomas appear to be linked to total lifetime sun exposure, melanoma development is most closely associated with intense, intermittent exposure [5][6][7][8][9]. A history of sunburn is often used as a surrogate measure for intense intermittent exposure.…”
Section: Uv Light and Melanomamentioning
confidence: 99%
“…However, long-term safety of such high-dose irradiation is difficult to predict at the moment. It is well accepted that sunburn, 15,16 especially in the earlier years of life, is associated with the development of melanomas in later years. Extended follow-up is thus warranted.…”
Section: Resultsmentioning
confidence: 99%